Future Directions: Analyzing Health Disparities Related to Maternal Hypertensive Disorders - Margaret Harris; Colette Henke; Mary Hearst; Katherine Campbell (Journal of Pregnancy)
Hypertensive disorders of pregnancy complicate up to 10% of pregnancies worldwide, constituting one of the most significant causes of maternal morbidity and mortality. Hypertensive disorders, specifically gestational hypertension, chronic hypertension, and preeclampsia, throughout pregnancy are contributors to the top causes of maternal mortality in the United States. Diagnosis of hypertensive disorders throughout pregnancy is challenging, with many disorders often remaining unrecognized or poorly managed during and after pregnancy. Moreover, the research has identified a strong link between the prevalence of maternal hypertensive disorders and racial and ethnic disparities. Factors that influence the prevalence of maternal hypertensive disorders among racially and ethnically diverse women include maternal age, level of education, United States-born status, nonmetropolitan residence, prepregnancy obesity, excess weight gain during pregnancy, and gestational diabetes. Examination of the factors that increase the risk for maternal hypertensive disorders along with the current interventions utilized to manage hypertensive disorders will assist in the identification of gaps in prevention and treatment strategies and implications for future practice. Specific focus will be placed on disparities among racially and ethnically diverse women that increase the risk for maternal hypertensive disorders. This review will serve to promote the development of interventions and strategies that better address and prevent hypertensive disorders throughout a pregnant woman’s continuum of care.